Early Netherlandish paintings : rediscovery, reception and research - Ridderbos, Bernhard; Buren, Anne van; Veen, Henk Th. van (Amsterdam : Amsterdam University Press, 2005)
An illustrated scholarly analysis of the art and the cultural interpretations of the Flemish Primitives.
Objects and Questions (Bernhard Ridderbos) -- Collecting Early Netherlandish Paintings in Europe and the United States (Till-Holger Borchert) -- From Waagen to Friedländer (Bernhard Ridderbos) -- Realism, Renaissance and Nationalism (Wessel Krul) -- Technical Examination (Jeltje Dijkstra) -- The Corpus of Fifteenth-Century Painting in the Southern Netherlands and the Principality of Liège (Henri Pauwels) -- Patronage (Maximiliaan P.J. Martens) -- Iconography and Iconology (Craig Harbison).
Includes bibliographical references and index.
English.
JSTOR
Keywords: Panel painting, Flemish -- 15th century; Panel painting, Flemish -- Expertising; Peinture sur panneau flamande -- 15e siècle.; ART -- History -- General; Panel painting, Flemish; Panel painting, Flemish -- Expertising; 1400-1499; Electronic books; Electronic books